Recent Advances in Underlying Pathologies Provide Insight into Interleukin-8 Expression-Mediated Inflammation and Angiogenesis - Basit Saleem Qazi; Kai Tang; Asma Qazi (International Journal of Inflammation)
Interleukin-8 has long been recognized to have anti-inflammatory activity, which has been established in various models of infection, inflammation, and cancer. Several cell types express the receptor for the cytokine IL-8 and upon its recognition produce molecules that are active both locally and systemically. Many different types of cells, in particular monocytes, neutrophils, epithelial, fibroblast, endothelial, mesothelial, and tumor cells, secrete IL-8. Increased expression of IL-8 and/or its receptors has been characterized in many chronic inflammatory conditions, including psoriasis, ARDS, COPD, and RA as well as many cancers, and its upregulation often correlates with disease activity. IL-8 constitutes the CXC class of chemokines, a potent chemoattractant and activator of neutrophils and other immune cells. It is a proangiogenic cytokine that is overexpressed in many human cancers. Therefore, inhibiting the effects of IL-8 signaling may be a significant therapeutic intervention.